The Role of Necropsy in Diagnostic Dilemmas as Seen in a Tertiary Hospital in North Central Nigeria - Olugbenga A. Silas; Adeyi A. Adoga; Agabus N. Manasseh; Godwin O. Echejoh; Barnabas M. Mandong; Rahila Olu-Silas (Journal of Tropical Medicine)
Background. Necropsy (autopsy) has helped medical science and law. It has given rise to numerous diagnostic surprises as it explains cause of death, pathogenesis of diseases, and circumstances of death. It also explains reasons for most therapeutic failures. In spite of its usefulness, the rate has dropped worldwide and Africa is worse hit. This work aims to highlight the role autopsy (Necropsy) plays in demystifying diagnostic dilemmas and to encourage its patronage by medical practitioners, law enforcement agents and society. Methods. This is a retrospective review of autopsy and clinical reports of cases seen by pathologists and physicians in the Jos University Teaching Hospital (JUTH), Jos, North central Nigeria. Results. A total 166 cases were studied out of which 52 had same diagnosis for both attending physician and pathologist, 106 had different diagnoses and in eight cases diagnoses remained unknown even after autopsy was performed. Conclusions. Autopsy remains an important tool for obtaining definitive diagnosis, determining cause of death to explain pathogenesis of diseases, medical auditing and a vital source of data for health statistics and planning.